Association of MAOA-uVNTR gene polymorphism with hostility in an open population of males aged 45-64 in Russia / Siberia (international program: WHO «MONICA-psychosocial», «HAPIEE») - V. V. Gafarov; E. A. Gromova; D. O. Panov; I. V. Gagulin; V. N. Maksimov; A. V. Gafarova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Objective: to study the association of hostility with high and low-active variants of the MAOA gene in an open population of men 45-64 years old. Using the methods proposed by the WHO International Program “MONICA-psychosocial” and “HAPIEE”, a representative sample of men aged 45–64 years old (n = 781 men, average age was 56.48 ± 0.2 years) in 2003-2005. All respondents independently completed a questionnaire on hostility. From the surveyed sample, using the random number method, 156 men were selected who were genotyped for MAOA-uVNTR polymorphism. It was approved that the level of hostility in the population of men was 60.3%. It was revealed that among persons with low-active alleles of the MAOA-L gene (allele 2 and 3) a high level of hostility was more common — 50.9%. The results of building a logistic regression model showed that the presence of low-active alleles (2; 3) of the MAOA gene increases the likelihood of hostility OR = 2,103 (95% CI 1,137-3,889, p = 0.018). The results obtained allow us to conclude that the low-active allele of the MAOA-L gene is associated with hostility.